2010
DOI: 10.1007/s00248-010-9685-7
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Efficient Identification of Agrobacterium Species by recA Allele Analysis

Abstract: The analysis of housekeeping recA gene sequences from 138 strains from 13 species or genomic species of Agrobacterium, nine being biovar 1 genomospecies, and the others Agrobacterium larrymoorei, Agrobacterium rubi, Agrobacterium sp. NCPPB 1650, and Agrobacterium vitis and one "former" Agrobacterium species, Rhizobium rhizogenes, led to the identification of 50 different recA alleles and to a clear delineation of the 14 species or genomospecies entirely consistent with that obtained by amplified fragment lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
89
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 34 publications
2
89
0
1
Order By: Relevance
“…The advantage of MLSA is that phylogenetic relationships of large sets of strains can be analyzed with better portability than any previous genotyping technique such as DNA/DNA hybridization, amplified fragment length polymorphism (AFLP), or repetitive sequence-based PCR (rep-PCR). It has also proven valuable for assessing phylogenetic relationships within complex species such as Stenotrophomonas maltophilia (36), Agrobacterium tumefaciens species complex (4,12), and Ralstonia solanacearum (11). The MLSA scheme we designed is based on six housekeeping genes routinely used for phylogenetic studies of Gram-positive bacteria belonging to Microbacterium, Aureobacterium (63), Lactobacillus (59), and Gram-negative bacteria (20,58,80,82).…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of MLSA is that phylogenetic relationships of large sets of strains can be analyzed with better portability than any previous genotyping technique such as DNA/DNA hybridization, amplified fragment length polymorphism (AFLP), or repetitive sequence-based PCR (rep-PCR). It has also proven valuable for assessing phylogenetic relationships within complex species such as Stenotrophomonas maltophilia (36), Agrobacterium tumefaciens species complex (4,12), and Ralstonia solanacearum (11). The MLSA scheme we designed is based on six housekeeping genes routinely used for phylogenetic studies of Gram-positive bacteria belonging to Microbacterium, Aureobacterium (63), Lactobacillus (59), and Gram-negative bacteria (20,58,80,82).…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that Agrobacterium fabrum, a species of the Agrobacterium tumefaciens species complex (20)(21)(22), has several species-specific regions in the genome, including the SpG8-1b region containing 15 different genes named atu1409 to atu1423. This region confers on A. fabrum the ability to degrade FA, since a mutant with the region deleted was no longer able to degrade the compound (23).…”
mentioning
confidence: 99%
“…S1 in the supplemental material). It is important to note in considering this analysis that strong evidence supports the reclassification of biovar II strains as Rhizobium (6,10,(16)(17)(18)(19). Our survey data indicate that linear chromosomes are unique to biovar I strains (see Table S5 in the supplemental material) (14,20).…”
mentioning
confidence: 98%
“…have traditionally been subdivided into three different groups, called biovars, based on differences in physiology and host range. Biovar I can be further subdivided into genomovars, with C58 belonging to genomovar 8 (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%